“Gendered space” a study of newspaper opinion journalism as emergent and oppositional to the dominant culture in journalism - Tabada, Ma. Theresa Angelina Q. (2022)
Access online through this link: https://www.plarideljournal.org/article/gendered-space-a-study-of-newspaper-opinion-journalism-as-emergent-and-oppositional-to-the-dominant-culture-in-journalism
Keywords: Creative nonfiction; Citizen journalism; Journalism and public opinion; Feminism